Phytochemical and Biological investigations of Phoenix paludosa Roxb. - Alam, Farzana; Rahman, Mohammad S; Alam, Md Shahanur; Hossain, Md Khalid; Hossain, Md Aslam; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Lupeol (1), epilupeol (2) and β-sitosterol (3) were isolated from the n-hexane and the carbon tetrachloride soluble fraction of a methanol extract of the leaves of Phoenix paludosa Roxb. The n-hexane, carbon tetrachloride and chloroform soluble materials from the concentrated methanol extract were subjected to antimicrobial screening and brine shrimp lethality bioassay. All of the partitionates showed insensitivity to microbial growth, while the n-hexane, chloroform and methanol soluble fractions showed significant cytotoxicity having LC50 2.17 μg/ml, 2.77 μg/ml and 2.46 μg/ml, respectively. This is the first report of isolation of the compounds 1-3 and bioactivities of P. paludosa. Key words: Phoenix paludosa; Aracaceae; Lupeol; Epi-Lupeol; β-sitosterol; Brine shrimp lethality bioassay; Antimicrobial. DOI: 10.3329/dujps.v8i1.5329 Dhaka Univ. J. Pharm. Sci. 8(1): 7-10, 2009 (June)